VẤN ĐỀ HÒA HỢP THỊ TRƯỜNG LÚA GẠO ĐBSCL KẾT QUẢ CỦA CHÍNH SÁCH TỰ DO HÓA THỊ TRƯỜNG LƯƠNG THỰC Ở VIỆT NAM - Hải, Lưu Thanh Đức (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract This article analyses the spatial price differences in the rice market of the Mekong Delta to assess the impact of the liberalisation policies on its functioning. The results of these policies carried out during the last two decades are impressive. The rice market system in the Delta is competitive. Price patterns strongly cohere and are integrated with the regulated export prices. However, price patterns in other regions and in particular in the North, are only weakly integrated with price patterns in the South. Private traders in the South satisfy local demand and deal with State Owned Enterprises (SOEs) involved in exports and transactions with the North. In the framework of the national food security policy, the state owned food companies subsidise transactions between the South and the North. Therefore, no profitable long distance trade can be established. Moreover, the state owned food companies acquire nearly all licences to export (quota). We conclude that, despite all the dramatic changes, the liberalisation process still faces major challenges. Title: Rice market integration in theMekongDelta the successful liberalisation of the domestic food market inViet Nam